INTEGRATION OF CHARACTER EDUCATION INTO ENGLISH LEARNING WITH THE USE OF CLASS DOJO APPLICATION AT NURUL AZMI’S SCHOOL - Titim Eliawati; Muthia Rafika (Journal MELT (Medium for English Language Teaching), 2021)
The research aims to find out the use of Class Dojo application to integrate character education into English learning at Nurul Azmi’s School. This research is a qualitative descriptive study. Data was collected through observation, interview and study documentation. Then data analyzed through three stages, namely data reduction, data presentation, and drawing conclusions. This study results concluded that (1) the ability of teachers to provide online learning through online can quickly develop if they get support from superiors through school policies, especially in conducting online learning. (2) the Class Dojo application really assist teachers in making learning reports; it also provides convenience for leaders in making strategic decisions only for learning purposes in the school as a whole.(3) development of online applications required by teachers and school management so that they can be adapted to the character of each class at Nurul Azmi's school.